A SOCIOLINGUISTIC ANALYSIS OF FREEDOM WRITERS MOVIE (EUFONI: Journal of Language, Literary, and Cultural Studies, 2019)
Language and society may influence each other. Study regarding the relationship between these two has always been interesting to conduct. This current research aims to see the use of language in its relation to social context used in a movie entitled â€œFreedom Writersâ€ and the factors behind it. This study used a descriptive qualitative method. The data were obtained from Freedom Writersâ€™ movie script which was taken from www.imsdb.com Freedom Writers Script â€“ Transcript from the Screenplay and/or the Hillary Swank Movie. First, the utterances by the characters were classified based on some linguistic features; phonology, morphology, syntax, as well as vocabulary. Then, they were analyzed to see how the characters, the white and the colored-people, used different versions of English to mark the identity of their social status in the society. The results show that there are some differences of linguistic features used by different groups of people based on their status in the society. These differences are caused by some factors. Apart from race, education level and social background are the factors that influence the forming of language styles used by a person.   Keywords: Sociolinguistic, Syntax, Morphology, Phonology, Freedom Writers Movie.